Development of Business Model Canvas Based on SWOT Analysis for the Family Segment to Increase Xl's Revenue - Haaris Millah Muhammad; Mohammad Riza Sutjipto (Journal Research of Social Science, Economics, and Management, 2025)
The Indonesian telecommunications industry is experiencing rapid transformation, with growing demands for efficient digital connectivity—particularly in the family segment. myXL, a prepaid application by XLSMART, offers significant potential to enhance family digital engagement but faces challenges in customer retention and feature optimization. Specifically, family-oriented packages such as AKRAB and XL Circle have not performed optimally as primary revenue drivers. This study adopts a qualitative approach using in-depth interviews with six key informants and analysis of internal company documents. Its objective is to evaluate the myXL prepaid business model and formulate strategies to increase revenue and customer engagement in the family segment. The study employs Business Model Canvas (BMC) analysis to map the current business structure, SWOT analysis to identify internal and external factors, and the TOWS Matrix to design strategic improvement scenarios. Findings reveal that the myXL application has strengths in digital infrastructure and active user loyalty but exhibits weaknesses in the adoption and popularity of family-specific features. Significant opportunities arise from increasing demand for family connectivity and digital parenting awareness, while threats include intense competition and regulatory changes. The study provides practical contributions for XLSMART in designing data-driven policies and digital product strategies. This research is limited to prepaid users of the myXL application in Indonesia